Eosin Y Catalyzed Visible-Light-Driven Aerobic Oxidative Cyclization of Thioamides to 1,2,4-Thiadiazoles - Srivastava, Vishnu P.; Yadav, Arvind K.; Yadav, Lal Dhar S. (Synlett, 2013)
A new approach for an efficient metal-free synthesis of 1,2,4-thiadiazoles from primary thioamides using visible light and air in the presence of eosin Y as a photoredox catalyst is reported. The protocol involves an aerobic oxidative cyclization of thioamides via the formation of C–N and C–S bonds to afford excellent yields of the products in a simple one-pot operation under mild conditions.
Keywords: visible light; eosin Y; photoredox; thioamides; cyclization; thiadiazoles